Molecular cloning of troponin i from the two-spotted cricket, Gryllus bimaculatus, and its expression pattern during starvation - Moon, Kyoungmin (2018)
There is few information about troponin gene expression by starvation in insect skeletal muscle and digestive tracts. The objective of this study was to perform molecular cloning of troponin I from the two-spotted cricket, Gryllus bimaculatus (GrybiTnI) and determine its expression patterns in three different skeletal muscles and digestive tracts during starvation. GrybiTnI was translated into a protein encoding 198 amino acids with a theoretical isoelectric point of 9.78 and a molecular weight of 23671.46 Da. The GrybiTnI has both the TnC-binding site and actin/TnC-binding site shown in the typical TnI amino acid sequences. Homology analysis revealed that GrybiTnI exhibited high similarity at the amino acid level to those of other insects already reported; 89~77% identity with those of other insects. Expression of GrybiTnI by starvation did not change in dorsal wing flight muscle and dorsal ventral flight muscle, but showed up-expression in dorsal longitudinal flight muscle. In the digestive tracts, the up-expression of GrybiTnI by starvation was observed only in the hindgut but not in the rest parts including Malpighian tubules. Re-feeding following starvation restored those expressions about the level before starvation in the dorsal longitudinal flight muscle and hindgut. In conclusion, troponin modulates gene expression not only to muscle elements but also to physiological changes such as strains. Â